2006
DOI: 10.1007/s11199-006-9010-6
|View full text |Cite
|
Sign up to set email alerts
|

Fallout from the Women’s Health Study: A Short-lived Vindication for Feminists and the Resurrection of Hormone Therapies

Abstract: The Women's Health Initiative studies were begun in 1997, in large part the result of women's health activists who for 40 years questioned the safety of hormone use at menopause and criticized the menopause as disease ideology. The studies were prematurely discontinued when investigators found that heretofore acclaimed benefits of hormone use were not supported. Risks to health such as stroke, breast cancer, and thrombophlebitis were found. A feeling of vindication was experienced by feminists but was quickly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Several examined changes across puberty in characteristics such as instrumentality and expressivity (Butcher 1989), intellectual abilities (Collins 1985), responsiveness to infants (Frodi et al 1984), body image (Ricciardelli and McCabe 2003), stereotypes about others' gendered personal-social attributes (Baruch 1975), and depression (Yuan 2007). Others discussed the limitations of the biomedical model of menopause, focusing on positive aspects of menopause (Derry 2002(Derry , 2006Voda and Ashton 2006).…”
Section: Other Coverage Of Biological Mechanisms Underlying Gendered mentioning
confidence: 99%
“…Several examined changes across puberty in characteristics such as instrumentality and expressivity (Butcher 1989), intellectual abilities (Collins 1985), responsiveness to infants (Frodi et al 1984), body image (Ricciardelli and McCabe 2003), stereotypes about others' gendered personal-social attributes (Baruch 1975), and depression (Yuan 2007). Others discussed the limitations of the biomedical model of menopause, focusing on positive aspects of menopause (Derry 2002(Derry , 2006Voda and Ashton 2006).…”
Section: Other Coverage Of Biological Mechanisms Underlying Gendered mentioning
confidence: 99%
“…These large, multi‐centre trials were part of the largest coordinated study of women's health ever undertaken by the U.S. National Institutes of Health. Although the WHI study was expected to run at least 10 years, the National Institutes of Health terminated a major clinical trial in June 2002 when unexpected results indicated increased risks of heart disease, strokes, blood clots and breast cancer for women using hormone therapies . As a result, the U.S. Preventive Services Task Force (USPSTF) concluded that the harms of post‐menopausal hormone therapies outweigh the benefits for chronic disease prevention…”
Section: Introductionmentioning
confidence: 99%
“…Although the WHI study was expected to run at least 10 years, the National Institutes of Health terminated a major clinical trial in June 2002 when unexpected results indicated increased risks of heart disease, strokes, blood clots and breast cancer for women using hormone therapies. 6 As a result, the U.S. Preventive Services Task Force (USPSTF) concluded that the harms of post-menopausal hormone therapies outweigh the benefits for chronic disease prevention. 7 In the light of the landmark decision to stop the WHI clinical trial early, there has been an explosion of 'media attention leading to confusion among women and health professionals about the benefits, risks and uncertainties' regarding hormone therapies.…”
mentioning
confidence: 99%
See 1 more Smart Citation